Historical Silences, Musical Noise: Slim Dusty, Country Music and Aboriginal history. Issue 2 (15th May 2020) - Martin, Toby
Abstract : Much Australian history has argued that Australian culture and academic writing were largely silent on the issue of Aboriginal history prior to 1968. Further, there has been a common argument—and assumption—that non-Indigenous country music did not deal with Indigenous Australians in this period at all. However, Australia's most popular recording artist, the country singer-songwriter, Slim Dusty, did in fact record several songs that dealt with issues such as the history of frontier massacres and Aboriginal pastoral labour during the 1950s and 1960s. These songs provide fascinating examples of alternative history-making, and show that there was a conversation—albeit limited—about difficult settler-colonial issues occurring in postwar popular culture. Dusty's songs also provide new ways of thinking about music and politics in the civil rights era, supplying rich examples of the ways in which popular music in general can engage with complex historical narratives, and how popular culture can disrupt conventional ways of telling history.